Reconfigurable Antennas and its recent developments - Dr. K Suman, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the fast growing research and development, the Radio Frequency front end should be conceptual in a natural scenario; reconfigurable antennas have become crucial, for the upcoming generation of wireless communication. Systems are sensible because of their ability to change the radiation characteristics dynamically. They have many advantages such as good isolation, out of band rejection, multifunctional capabilities, low volume, low front end processing efforts without the need for filtering element which made them useful in wireless communications applications such as fourth-generation (4G) and fifth-generation (5G) mobile terminals. Reconfigurable antennas threw a novel challenge to antenna designers and researchers as they can be tuned to any frequency of operation without changing the radiation pattern. For the past three decades lot of improvement was done in the advancement of reconfigurable antennas. This review paper emphasizes the recent advancements in reconfigurable antennas..